HVC contributes toward conspecific contact call responding in male Bengalese finches. Issue 7 (4th May 2016) - Urbano, Catherine M.; Aston, Avery E.; Cooper, Brenton G.
Abstract : The processes of producing and acquiring birdsong, like human speech, utilize interdependent neural systems for vocal learning and production. In addition to song, these brain areas are undoubtedly used for other affiliative behaviors. Oscine sound production is lateralized because their vocal organ contains two independently controlled sound sources. Therefore, songbirds offer a unique opportunity to study the biological relevance of lateralized behavioral control. Bengalese finches ( Lonchura striata domestica ) produce different types of sound with each sound source: the left sound generator produces tonal frequencies from 1 to 4 kHz and the right sound source produces the lower frequency (<2 kHz) tonal and broadband sounds. We sought to investigate whether the premotor nucleus HVC contributes toward lateralized auditory processing of conspecific vocalizations. We ablated either the left or the right HVC and tested birds with the callback paradigm using female contact calls that were filtered to accentuate particular frequency ranges. The results show that (a) the acoustic frequency of call stimuli drives different patterns of calling behavior and that (b) both HVC nuclei contribute toward contact call production, but HVC ablation does not alter the number of short calls produced upon hearing a female contact call. These data are consistent with the emerging view that the motor production and auditory processing are linked and suggest that HVC may contribute toward affiliative behaviors by promoting the production of contact call responses. Abstract : Supplemental Digital Content is available in the text.